Gender differences in peak medial joint contact forces during activities of daily living - Samantha J. Snyder; Maliheh Fakhar; Jae Kun Shim; Ross H. Miller (PeerJ, 2025)
Women are more likely to suffer from knee osteoarthritis as compared to men. For men and women, greater peak knee medial joint contact force is associated with greater rates of knee osteoarthritis. However, it is unclear if the increased rates of knee osteoarthritis in women is associated with greater medial joint contact force. We hypothesize that because women experience greater rates of knee osteoarthritis, they would experience greater peak medial joint contact force. Fifty-two healthy, young participants (26 women, 26 men) performed sit-to-stand, stand-to-sit, self-selected speed walking, self-selected speed running, and set speed running trials over force plates while motion capture data was recorded. Medial joint contact force, scaled by bodyweight, was calculated with a reduction modeling approach from inverse dynamics data and ultrasound measured distances. Differences in peak medial joint contact force between men and women were tested with one-tailed unpaired Student’s t-tests with a Bonferroni correction. No significant differences were seen between groups peak medial joint contact force in any of the tested movements. Medial joint contact force may not be able to explain the disparity in knee osteoarthritis rates between men and women.